Some Relationships Among Thermal Properties, Detonation Parameters and Sensitivity of Nitramine Fillers in Formex Based PBXs - Qi-Long YAN (Wojskowa Akademia Techniczna, 2013)
Thermal behavior and decomposition kinetics of formex-bonded PBXs based on some attractive cyclic nitramines (BCHMX, HMX, RDX and CL-20) were investigated by means of nonisothermal Thermogravimetry (TG) and Differential Scanning Calorimetry (DSC). Besides, their detonation parameters have been calculated by EXPLO 5 code. It was found that the effect of formex polymer base on thermal decomposition of HMX is different from other cyclic nitramines, namely, the formex base could increase the activation energy of HMX while decrease that of others. Besides, the logarithm of volume heat of detonation for formex based explosives is linearly dependent on their time constant of initiation. Furthermore, on one hand, except for RDX, the heat of detonation decreases with the increase of activation energy, and the spark energy and impact energy of cyclic nitramine fillers decreases with the increase of the critical temperature of their PBXs. On the other hand, except for HMX, the rate constant of PBXs is linearly dependent on the impact sensitivity of their pure nitramine fillers.
Keywords: Właściwości detonacyjne materiałów wybuchowych